2021
DOI: 10.3389/fphar.2021.651444
|View full text |Cite
|
Sign up to set email alerts
|

4-OI Attenuates Carbon Tetrachloride-Induced Hepatic Injury via Regulating Oxidative Stress and the Inflammatory Response

Abstract: The liver is an important metabolic organ, and acute liver injury (ALI) is potentially lethal. Itaconate, a metabolic intermediate from the tricarboxylic acid cycle, showed emerging anti-oxidative and anti-inflammation properties, and an accumulating protective effect in multiple diseases, but its role in ALI still needs to be further explored. Here we established an ALI model induced by carbon tetrachloride in mice. Our results showed that 4-Octyl itaconate (OI), a derivate of itaconate, mitigated hepatic dam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 61 publications
1
23
0
Order By: Relevance
“…Additionally, OI, a derivate of itaconate, showed a protective effect in the hepatic ischemia-reperfusion injury murine model [ 12 ]. Moreover, our previous publication showed that OI protected mice from carbon tetrachloride-induced hepatic injury [ 22 ]. Nonetheless, the mechanism of liver injury is different in different pathogenic models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, OI, a derivate of itaconate, showed a protective effect in the hepatic ischemia-reperfusion injury murine model [ 12 ]. Moreover, our previous publication showed that OI protected mice from carbon tetrachloride-induced hepatic injury [ 22 ]. Nonetheless, the mechanism of liver injury is different in different pathogenic models.…”
Section: Discussionmentioning
confidence: 99%
“…RAW264.7 and NCTC 1469 were grown in 6-well plates to 40-50% confluent. Then, 50 nM Nrf2 siRNA or control siRNA was transfected with Lipofectamine 6000 as we reported before [ 22 ]. The cells were used for the next experiments 48 h after transfection.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have confirmed that Nrf2 activation played an important role in alleviating liver injury [23,24]. For example, we previously found that Nrf2 activation mitigated carbon tetrachloride-induced hepatic injury by inhibiting oxidative stress and inflammation [24]. Furthermore, OI mitigated ischemia-reperfusion injury-induced liver injury by activating the Nrf2 pathway [25].…”
Section: Introductionmentioning
confidence: 56%
“…Moreover, Nrf2 was recently found to bind with the promoter regions of some proinflammatory cytokines such as interlukin-6 (IL-6) and directly inhibit their transcription to alleviate the inflammatory response [22]. Previous studies have confirmed that Nrf2 activation played an important role in alleviating liver injury [23,24]. For example, we previously found that Nrf2 activation mitigated carbon tetrachloride-induced hepatic injury by inhibiting oxidative stress and inflammation [24].…”
Section: Introductionmentioning
confidence: 92%
“…Normally, Nrf2 is combined with Kelch-like ECH-associated protein 1 (Keap1) to form a complex. Oxidative injury and other stress conditions could lead to keap1-Nrf2 dissociation [15]. Then, Nrf2 translocate from the cytoplasm into the nucleus and activate antioxidative genes such as heme oxygenase-1 (HO-1) and NAD(P)H:quinone oxidoreductase 1 (NQO1), which could generate cytoprotective effects [16].…”
Section: Introductionmentioning
confidence: 99%